Anesthetic drug midazolam inhibits cardiac human ether-à-go-go-related gene channels: mode of action - Vonderlin N; Fischer F; Zitron E; Seyler C; Scherer D; Thomas D; Katus HA; Scholz EP (Dove Medical Press, 2015)
Nadine Vonderlin,1 Fathima Fischer,1 Edgar Zitron,1,2 Claudia Seyler,1 Daniel Scherer,1 Dierk Thomas,1,2 Hugo A Katus,1,2 Eberhard P Scholz1 1Department of Internal Medicine III, University Hospital Heidelberg, 2German Centre for Cardiovascular Research, Partner Site Heidelberg/Mannheim, Heidelberg, Germany Abstract: Midazolam is a short-acting benzodiazepine that is in wide clinical use as an anxiolytic, sedative, hypnotic, and anticonvulsant. Midazolam has been shown to inhibit ion channels, including calcium and potassium channels. So far, the effects of midazolam on cardiac human ether-à-go-go-related gene (hERG) channels have not been analyzed. The inhibitory effects of midazolam on heterologously expressed hERG channels were analyzed in Xenopus oocytes using the double-electrode voltage clamp technique. We found that midazolam inhibits hERG channels in a concentration-dependent manner, yielding an IC50 of 170 µM in Xenopus oocytes. When analyzed in a HEK 293 cell line using the patch-clamp technique, the IC50 was 13.6 µM. Midazolam resulted in a small negative shift of the activation curve of hERG channels. However, steady-state inactivation was not significantly affected. We further show that inhibition is state-dependent, occurring within the open and inactivated but not in the closed state. There was no frequency dependence of block. Using the hERG pore mutants F656A and Y652A we provide evidence that midazolam uses a classical binding site within the channel pore. Analyzing the subacute effects of midazolam on hERG channel trafficking, we further found that midazolam does not affect channel surface expression. Taken together, we show that the anesthetic midazolam is a low-affinity inhibitor of cardiac hERG channels without additional effects on channel surface expression. These data add to the current understanding of the pharmacological profile of the anesthetic midazolam. Keywords: midazolam, anesthetics, human ether-à-go-go-related gene, potassium channels